Effect of Basal Metabolic Rate on Cancer: A Mendelian Randomization Study - Ng, Jack C. M.; Schooling, C. Mary (Frontiers in Genetics, 2021)
Background: Basal metabolic rate is associated with cancer, but these observations are open to confounding. Limited evidence from Mendelian randomization studies exists, with inconclusive results. Moreover, whether basal metabolic rate has a similar role in cancer for men and women independent of insulin-like growth factor 1 increasing cancer risk has not been investigated. Methods: We conducted a two-sample Mendelian randomization study using summary data from the UK Biobank to estimate the causal effect of basal metabolic rate on cancer. Overall and sex-specific analysis and multiple sensitivity analyses were performed including multivariable Mendelian randomization to control for insulin-like growth factor 1. Results: We obtained 782 genetic variants strongly (p-value <5x10-8) and independently (r2 <0.01) predicting basal metabolic rate. Genetically predicted higher basal metabolic rate was associated with an increase in cancer risk overall (odds ratio, 1.06; 95% confidence interval, 1.02-1.10) with similar estimates by sex (odds ratio for men, 1.07; 95% confidence interval, 1.002-1.14; odds ratio for women, 1.06; 95% confidence interval, 0.995-1.12). Sensitivity analyses including adjustment for insulin-like growth factor 1 showed directionally consistent results. Conclusion: Higher basal metabolic rate might increase cancer risk. Basal metabolic rate as a potential modifiable target of cancer prevention warrants further study.